2015
DOI: 10.5114/ceji.2015.54604
|View full text |Cite
|
Sign up to set email alerts
|

Long-term valacyclovir treatment and immune modulation for Herpes-associated erythema multiforme

Abstract: ObjectiveErythema multiforme (EM) is an immune-mediated condition characterized by the appearance of target-like lesions on the skin and often accompanied by erosions or bullae involving the oral, genital, and/or ocular mucosae. 70% of recurrent EM cases are associated with HSV reactivation and it is labelled as herpes-associated erythema multiforme (HAE M). Recurrences are seen in approximately 20-25% of EM cases and managing these conditions are challenging for both the patient and the doctor. The effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…A double‐blind placebo‐controlled trial showed acyclovir to be effective in the treatment of recurrent EM in adults . Although remission of recurrent EM has been reported with antiviral medications with greater bioavailability, such as valacyclovir and famciclovir, in adult cases unresponsive to acyclovir, the results of the aggregate analysis in pediatric recurrent EM suggest little difference . The proportion of patients achieving CR with continuous antivirals was similar to those in previous reports in pediatric and general populations.…”
Section: Discussionmentioning
confidence: 90%
“…A double‐blind placebo‐controlled trial showed acyclovir to be effective in the treatment of recurrent EM in adults . Although remission of recurrent EM has been reported with antiviral medications with greater bioavailability, such as valacyclovir and famciclovir, in adult cases unresponsive to acyclovir, the results of the aggregate analysis in pediatric recurrent EM suggest little difference . The proportion of patients achieving CR with continuous antivirals was similar to those in previous reports in pediatric and general populations.…”
Section: Discussionmentioning
confidence: 90%
“…Echinacea purpurea ( E. purpurea ), a member of the Asteraceae family, is a plant possessing medicinal properties . The use of E. purpurea , herbs native to the North American prairies, has a long history . E. purpurea has been used in Europe and America for the treatment of different ailments such as bug and mosquito bites, now is shown to be safe and effective in the prevention of the common cold and respiratory infections .…”
Section: Introductionmentioning
confidence: 99%
“…EM is self‐limiting and usually heals in 1–2 weeks, but it is possible to have periodic episodes. More in detail, 20–25% cases of HAEM show recurrences, caused by periodic reactivations of HSV (Staikuniene & Staneviciute, ).…”
Section: Discussionmentioning
confidence: 99%